2022
DOI: 10.1073/pnas.2212870119
|View full text |Cite
|
Sign up to set email alerts
|

The unstructured linker of Mlh1 contains a motif required for endonuclease function which is mutated in cancers

Abstract: Eukaryotic DNA mismatch repair (MMR) depends on recruitment of the Mlh1-Pms1 endonuclease (human MLH1-PMS2) to mispaired DNA. Both Mlh1 and Pms1 contain a long unstructured linker that connects the N- and carboxyl-terminal domains. Here, we demonstrated the Mlh1 linker contains a conserved motif ( Saccharomyces cerevisiae residues 391–415) required for MMR. The Mlh1-R401A,D403A-Pms1 linker motif mutant protein was defective for MMR and endonuclease activity in vitro, even though the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Reanalysis of lysine crosslinking of S. cerevisiae Mlh1-Pms1 in the absence of ATP and DNA (Figure 4A) [49] suggests that the linker motif interacts with the Mlh1-Pms1 CTDs. Several sets of crosslinks can be explained by motif-CTD interactions combined with Mlh1 CTD wrapping by the Pms1 linker as observed using in silico modeling (Figure 4B) [35] : The cladogram is based on previous analyses. [43] (B) The conserved linker motif from the alignment of selected Mlh1 sequences; yellow highlighted residues are conserved and red highlighted residues are at −0/−2 sequence difference.…”
Section: Does the Linker Motif Interact With A Protein Component Of Mmr?mentioning
confidence: 95%
See 1 more Smart Citation
“…Reanalysis of lysine crosslinking of S. cerevisiae Mlh1-Pms1 in the absence of ATP and DNA (Figure 4A) [49] suggests that the linker motif interacts with the Mlh1-Pms1 CTDs. Several sets of crosslinks can be explained by motif-CTD interactions combined with Mlh1 CTD wrapping by the Pms1 linker as observed using in silico modeling (Figure 4B) [35] : The cladogram is based on previous analyses. [43] (B) The conserved linker motif from the alignment of selected Mlh1 sequences; yellow highlighted residues are conserved and red highlighted residues are at −0/−2 sequence difference.…”
Section: Does the Linker Motif Interact With A Protein Component Of Mmr?mentioning
confidence: 95%
“…Bars above indicate mutations causing full (purple), partial (green) or no (blue) MMR defects. [23,35,60,61] Vertical hashes indicate residues equivalent to DNA contacting residues in each subunit (MutL A and MutL B ) of the E. coli MutL-DNA structure. [58] Sites of S. cerevisiae Mlh1 adjacent to DNA in a Mlh1-Mlh3 bound to a Holliday junction [23] are indicated by squares.…”
Section: Does the Linker Motif Interact With Dna?mentioning
confidence: 99%
“…Among the different proteins that suffer dysregulated post-translational methylation associated with CRC ( Table 2 ), the one that is involved in cell growth suppression has downregulated methylation (putative insulin-like growth factor 2 antisense gene protein) [ 44 , 45 ]. The other proteins identified have an upregulated methylation, among them are (1) BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 that is involved in apoptosis [ 46 ]; (2) homeobox protein CDX-2 that is involved in the transcriptional regulation of different genes expressed in the intestine [ 47 ]; (3) C-X-C motif chemokine 14 that is involved in immunoregulatory and inflammatory processes [ 48 ]; (4) transcription factor E2F1 that participates in the cell cycle [ 49 ]; (5) DNA mismatch repair protein Mlh1 that participates in DNA repair [ 50 ]; (6) nuclear factor NF-kappa-B p105 subunit that is a pleiotropic transcription factor involved in several signal transduction events which are initiated by stimuli such as oxidative stress or inflammation [ 51 ]; and (7) 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 that is an essential protein for cell cycle progression and apoptosis prevention [ 52 ].…”
Section: Post-translational Modifications In Colorectal Cancermentioning
confidence: 99%
“…Recent research identified an evolutionarily conserved stretch of amino acids in the linker of the yeast Mlh1 protein that is essential for endonuclease activity in vitro and MMR in vivo. 3 The paper by Put-…”
Section: Dna Mismatch Repair Endonuclease Intrinsically Disordered Re...mentioning
confidence: 99%
“…Recent research identified an evolutionarily conserved stretch of amino acids in the linker of the yeast Mlh1 protein that is essential for endonuclease activity in vitro and MMR in vivo 3 . The paper by Putnam and Kolodner in this issue of BioEssays 4 presents an intriguing hypothesis to explain the role of this motif in licencing endonuclease activity during eukaryotic MMR.…”
mentioning
confidence: 99%